Environmentally friendly concrete material with early strength and fast hardening using coal as an aggregate: a case for supporting empty roadways - Wang, Hanqiu; Shi, Yannan; Zhao, Jiawei; Wang, Yiying; Liu, Chengyong; Wu, Yuyi (Frontiers in Materials, 2023)
In order to facilitate ventilation or transportation, many coal mines usually excavate an empty roadway in the middle of the mining working face. Under the influence of mining pressure, empty roadways are easily damaged, seriously threatening coal mines' safety. Because the traditional support method of the empty roadway has the problems of low efficiency, high cost, and low strength, this paper researches the coal-based concrete support material with better effect. The grading test of coal aggregate was carried out, and it was found that the percentage of small-size aggregate greatly influenced the reduction of aggregate porosity in the stacked state.To solve the problems of the high cost of strengthening support methods such as high water material support in empty roadways, which could be more conducive to recovery and reduce coal quality. The research on empty roadways supports concrete material with coal as aggregate, making the working face recover coal resources safely and efficiently. The optimum gradation test of the total is to enhance the strength of support and solve the problem of low power and difficult cementation of coal. Based on the hydration analysis of cementitious material, the coal-based concrete, mainly composed of low-cost slag, is determined. The cementitious material with simple composition, rapid setting, and fast hardening was found. It is proved that the mechanical properties and molding effect of coal-based concrete support composed of gypsum, GGBFS, and clinkercement are better than those of commercial cement. The structural model of "surrounding rock-empty roadways-coal pillar-support" is established. The calculation method and check basis of empty roadways support resistance N1 are obtained. The results of industrial application verified that coal-based concrete could effectively protect empty roadways without affecting the productivity of coal mines.The characteristics of coal-based concrete mold for empty roadways support 设置了格式: 字体: 倾斜 设置了格式: 下标 2 This is a provisional file, not the final typeset article are introduced. It provides a reference for the construction design and application of coal-based concrete in empty roadways. It can be used for reference to similar engineering problems.